Perancangan Website Sebagai Optimalisasi Media Promosi Sekolah Dasar Swasta Duri Indah Jakarta - Pepi Permatasari; Sri Wahyuningsih; Lies Andayani; Wahyumi Ekawanti (Universitas Muhammadiyah Manado, 2024)
Websites are the cheapest, most effective and efficient promotional media, because websites are online publication media for schools which are a necessity in providing information about products, price discounts and others and can also receive information quickly and accurately. SDS Duri Indah Jakarta until 2023 will always provide information regarding school activities and information regarding registration of new students via social media. Initial observations at SDS Duri Indah, the school does not yet have an independent website, so it is necessary to create and develop a website with the school domain (.sch). This website helps schools carry out promotions. Creation and assistance activities use several methods, namely 1) Observation, 2) Website creation, 3) Assistance with website management, 4) Monitoring and evaluation. The result of the activity is that the school has a school website and can also provide knowledge about managing school websites for admins and how to create articles and content for users.